Evolutionary and Epidemiological Implications of Multiple Infection in Plants. (January 2016) - Tollenaere, Charlotte; Susi, Hanna; Laine, Anna-Liisa
Abstract : Recent methodological advances have uncovered tremendous microbial diversity cohabiting in the same host plant, and many of these microbes cause disease. In this review we highlight how the presence of other pathogen species, or other pathogen genotypes, within a plant can affect key components of host–pathogen interactions: (i) within-plant virulence and pathogen accumulation, through direct and host-mediated mechanisms; (ii) evolutionary trajectories of pathogen populations, through virulence evolution, generation of novel genetic combinations, and maintenance of genetic diversity; and (iii) disease dynamics, with multiple infection likely to render epidemics more devastating. The major future challenges are to couple a community ecology approach with a molecular investigation of the mechanisms operating under coinfection and to evaluate the evolution and effectiveness of resistance within a coinfection framework. Trends: Molecular tools are becoming readily available for the study of parasites. These technical advances have shown that multiple infection is common in the wild and in agriculture, with the same host individual simultaneously infected by several pathogen genotypes or species (i.e., coinfection). Under coinfection, pathogens may interact either directly (mechanical or chemical interactions) or indirectly through host resources or defenses. These direct or host-mediated interactions under coinfection can change virulence, within-host pathogen accumulation, and transmission. Such plant-level effects can also be seen at the population level, with coinfection rendering epidemics more devastating. Coinfection may drive the evolutionary trajectories of pathogen populations through its effects on virulence evolution and on the generation and maintenance of genetic diversity in pathogen populations.